Synthesis of novel aryl brassinosteroids through alkene cross-metathesis and preliminary biological study - Korinkova, Petra; Bazgier, Vaclav; Oklestkova, Jana; Rarova, Lucie; Strnad, Miroslav; Kvasnica, Miroslav (Steroids, 2017)
A series of phenyl analogues of brassinosteroids was prepared via alkene cross-metathesis using commercially available styrenes and 24-nor-5α-chola-2,22-dien-6-one. All derivatives were successfully docked into the active site of BRI1 using AutoDock Vina. Plant growth promoting activity was measured using the pea inhibition biotest and Arabidopsis root sensitivity assay and then was compared with naturally occuring brassinosteroids. Differences in the production of plant hormone ethylene were also observed in etiolated pea seedlings after treatment with the new and also five known brassinosteroid phenyl analogues. Antiproliferative activity was also studied using normal human fibroblast and human cancer cell lines.
Keywords: hrách setý; Arabidopsis Proteins; techniky syntetické chemie; Molecular docking; BRI1 receptor kinase; Pisum sativum; Brassinosteroids; simulace molekulového dockingu; Organic synthesis; alkeny; proteinkinasy; Chemistry Techniques, Synthetic; proteiny huseníčku; Cross-metathesis; Plant bioassays; Alkenes; katalytická doména; Catalytic Domain; Protein Kinases; Arabidopsis; Molecular Docking Simulation; brassinosteroidy